2019
DOI: 10.14738/assrj.69.7109
|View full text |Cite
|
Sign up to set email alerts
|

Tax Revenue and Economic Development in Nigeria

Abstract: This study investigated the impact of taxation on economic development of Nigeria from 2003 to 2017.Vector Error Correction Model (VECM), Augmented Dickey-Fuller (ADF) unit root test, Autoregressive Distributed Lag (ARDL) bounds test, Jarque-Bera Normality Test and Eigenvalue stability condition were utilised in this study. The study revealed that companies’ income tax, petroleum profit and value added tax have a long run impact of -0.225(p-value=0.000),-0.0005 (p-value=0.699), and 0.211(p-value=0.000) respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This is in line with the a priori expectation. The finding is in agreement with that of many others including Okeke et al (2018), Ufoegbu et al (2016), Nwakanma andNnamdi (2013), andEwa et al (2020); but at variant with the findings of authors such as Olaoye et al (2019), andIdeh (2019). Since economic development is proxy by the human development index (HDI), revenue from petroleum profit tax raised per capita income, and increased literacy rate and life expectancy in Nigeria within the period under study.…”
Section: Long-run and Short-run Estimation Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with the a priori expectation. The finding is in agreement with that of many others including Okeke et al (2018), Ufoegbu et al (2016), Nwakanma andNnamdi (2013), andEwa et al (2020); but at variant with the findings of authors such as Olaoye et al (2019), andIdeh (2019). Since economic development is proxy by the human development index (HDI), revenue from petroleum profit tax raised per capita income, and increased literacy rate and life expectancy in Nigeria within the period under study.…”
Section: Long-run and Short-run Estimation Resultssupporting
confidence: 93%
“…They suggested that the country's tax base be widened to raise more money through taxes. The effect of taxes on Nigeria's economic development from 2003 to 2017 was examined by Olaoye et al (2019). The HDI served as a stand-in for economic development.…”
Section: Review Of Related/empirical Literaturementioning
confidence: 99%
“…Furthermore, the results of the stamp duty variable show a significant negative effect on the economic growth of Nigeria. The result is confirmation that taxation is still a powerful socio-political and economic tool for economic growth and national prosperity [25] . Tax evasion is a global concern, but it appears to be common when compared to the prevalence of corrupt practices.…”
Section: Conclusion and Recommendationsmentioning
confidence: 65%
“…Their findings revealed that in Nigeria, longrun taxes on economic growth are more pronounced than short-run taxes [24] . From 2003 to 2017, the study investigated the impact of taxation on Nigerian economic development [25] . They employed the Vector Error Correction Model (VECM), the Augmented Dickey-Fuller (ADF) unit root test, the Autoregressive Distributed Lag (ARDL) bounds test, the Jarque-Bera Normality Test, and the Eigenvalue Stability Condition Test.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…dev is 0.068755, T-value is 1.130473, and probability value is 0.3405, which explains an indirect and insignificant relation between tax revenue and GDP in Kenya (Amin et al, 2021). [ 23 ] value is -0.979269, Std.dev value is 0.009127, t-value is 129.2094 and probability values is 0.0000. The coefficient value of FDI is 0.451639, Std.…”
Section: Effect Of the Tax Rate On Economic Growth: A Panel Analysismentioning
confidence: 95%